Ecological responses to climate extremes in a mesic grassland - Hoover, David Lewis, author; Knapp, Alan K., advisor; Smith, Melinda D., committee member; Bauerle, William L., committee member; von Fischer, Joseph C., committee member (Colorado State University. Libraries, 2014)
Climate change threatens ecosystems through altered climate means and by increasing the frequency and intensity of extreme climatic events. Such events may have greater impacts on ecosystems than shifting means alone because they can push organisms beyond critical thresholds. Thus, there is an urgent need to assess the response of ecosystems to climate extremes as well as elucidate the mechanisms underlying the observed responses. My dissertation examined the ecological impacts of two years of experimentally imposed climate extremes (heat waves and drought) followed by a recovery year, on a mesic tallgrass prairie grassland ecosystem. The broad objectives of this research were (1) to assess the resistance and resilience of this ecosystem to the individual and combined effects of heat waves and drought, and (2) to identify the ecological mechanisms driving the responses and (3) to evaluate the sensitivities of key carbon cycling process to heat waves and drought. I measured a range of biotic responses to these treatments including: ecophysiology, community dynamics, primary production, and soil respiration in order to gain a comprehensive understanding how this ecosystem responds to such extremes. During the first year of the experiment, I examined the ecophysiological and productivity responses of the dominant C4 grasses to a growing season-long drought and a midsummer, two-week heat wave. Although differential sensitivities were apparent, the independent effects of drought dominated the ecological responses for both species, with only minor direct effects of heat were observed. However, the heat wave treatments had indirect effects via enhanced soil drying, making it difficult to separate the effects of the heat wave and precipitation treatments on biotic responses. Therefore in the second year of the experiment, I controlled for heat-induced water losses during the heat wave and examined the independent effects of heat on net photosynthesis in both grass species under contrasting soil moisture regimes. Under low soil moisture, heat had no effect on net photosynthesis, while increasing temperatures moderately reduced photosynthesis under high soil moisture. Next I examined the resistance and resilience in ecosystem function (aboveground primary production) of this tallgrass prairie to the two years of extreme treatments and for one subsequent recovery year. I observed high resistance to heat but not drought, as aboveground production dropped below historic levels during the second year of the drought. Despite this extreme ecological response, productivity fully recovered in just one year post-drought due to rapid demographic compensation by the dominant grass offsetting the loss of the dominant forb. Finally, I examined the response of soil respiration to heat and drought across the three years of the experiment. As with aboveground net primary production, soil respiration was more sensitive to drought than heat, but it was less sensitive overall to drought than production. There are three main conclusions from my dissertation research. First, this tallgrass prairie ecosystem has low resistance but high resilience to extreme short-term drought, which may be an important characteristic for long-term stability in ecosystems with histories of drought. Secondly, the two most abundant species governed both community and ecosystem-level dynamics across this three-year experiment, providing evidence for the central role of dominant species during these short-term events. Finally, my results suggest that three key carbon cycling processes in this mesic grassland - photosynthesis, plant productivity and soil respiration - are all significantly more sensitive to the independent effects of an extreme drought than heat waves and there were little to no combined effects of heat waves and drought. Overall, these results suggest that in a future with more frequent and extreme heat waves and drought, this mesic grassland will be most vulnerable to water stress, either directly through precipitation deficits or indirectly through warming-induced drying, while the direct ecological effects of midsummer heat waves will be minor.
Keywords: climate extremes; dominant species; drought; ecosystem function; grassland; heat waves